The Influence of Intellectual Capital and Bank-Specific Factors on Profitability in Sharia Commercial Banks in Indonesia for the 2015-2023 Period - Gita Amalia Putri; Ruhadi Ruhadi; Destian Arshad Darulmalshah Tamara; Muhammad Syaiful (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
This study aims to determine the effect of intellectual capital and bank-specific factors on profitability in Islamic commercial banks. Intellectual capital consists of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Relational Capital Efficiency (RCE), and Capital Employed Efficiency (CEE). Bank-specific factors are proxied by the Financing to Deposit Ratio (FDR) and Operating Expenses to Operating Income (BOPO), while profitability is proxied by Return on Assets (ROA). The study population consists of Islamic commercial banks registered with the Financial Services Authority (OJK) from 2015 to 2023. The number of Islamic commercial banks included in the sample is eight Islamic commercial banks. The research method used is a quantitative method employing panel data regression analysis. The results of this study indicate that Capital Employed Efficiency (CEE) has a positive and significant effect on Return On Assets (ROA). Conversely, Human Capital Efficiency (HCE) and Operating Expenses to Operating Income (BOPO) have a negative and significant effect on Return on Assets (ROA). Meanwhile, Structural Capital Efficiency (SCE), Relational Capital Efficiency (RCE), and Financing to Deposit Ratio (FDR) do not have a significant effect on Return on Assets (ROA).